If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-x-5=2(x+)-9
We move all terms to the left:
3x-x-5-(2(x+)-9)=0
We add all the numbers together, and all the variables
3x-x-(2(+x)-9)-5=0
We add all the numbers together, and all the variables
2x-(2(+x)-9)-5=0
We calculate terms in parentheses: -(2(+x)-9), so:We get rid of parentheses
2(+x)-9
We multiply parentheses
2x-9
Back to the equation:
-(2x-9)
2x-2x+9-5=0
We add all the numbers together, and all the variables
4!=0
There is no solution for this equation
| c=37.17+0.25 | | 13x=12+9x/13 | | 9(x-4)-2=-38 | | 3x=8+6x/3 | | 3.54x-2=^2 | | X+7=-x+21 | | Y=-8=4(x+3) | | a+(-21)=30 | | 24=3(2p-7)-1p | | 24=h/18-16-4 | | X+11=5x+27 | | A={x/x=-2}B={x/x4} | | -2p=-5p-18 | | -4p=-7p+12 | | 5p=-p+12 | | 7-3x=3-1x | | 5-1x=2x-7 | | 3(x-9)-2(x+4)=6x | | 7+3x=11-1x | | 14=-(p-8$ | | 5q/4=10 | | 3^(y-1)=9^y | | -5x+4=-2x+10+4x | | 3^y-1=9^y | | 12-6z=10-6z | | 4m/5+1=6 | | 4m-24=0 | | 4m-7=31 | | z-9=+15 | | -82=2(7p+1) | | 50+5x=82.5 | | 25+49.05x=60+42.05 |